Sistem Elisitasi Kebutuhan dengan Konsep Gamification Berbasis Website - Fadhilah Muchammad F. A. Bakthier; Fajar Pradana; Bayu Priyambadha (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Requirements elicitation is an important process in software engineering that used to get information about the system scope and needs that will be built. This elicitation process determines the success of the software, where if there is an error in defining the requirements it will cause system to failure. In this process the stakeholders' role is needed to help the software development team determine what kind of system will be built. But, in the process there are several problems that can hinder the elicitation process. The first problem is that stakeholders usually having trouble when defining the desired system and the lacks of knowledge that the development team have about scope of the system, caused a misunderstanding in defining the requirements. On the other hand, the low enthusiasm of stakeholders makes the requirements elicitation proses has been more difficult, so the requirements that been produced has a poor quality. Based on these problems, need an innovation in the process of elicitation to overcome existing problems. The gamification concept is the way that can be done to make an activity more interesting, so that it can increase the stakeholders' enthusiasm to participate in the process of requirements elicitation. The requirements elicitation system with gamification concept is expected to be able to make collaboration between stakeholders and the development team easier, therefore they can produce a requirement with a good quality. This system is made with website technology and has been tested with the Whitebox testing method for unit testing and integration testing, and the Blackbox testing method for validation testing which resulting in a 100% valid value for all test cases then, usability testing which resulting in 82.5 with acceptable category.